Quyền tiếp cận thông tin và những biện pháp bảo đảm tiếp cận thông tin theo quy định của Luật Thư viện - Lê, Tùng Sơn (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Access to information is both a political right and a civil right of every citizen as prescribed by the 2013 Constitution. Through the provisions of the Library Act, citizens’ right to access to information is concretized by provisions on citizens' rights to access information and use information products and services in libraries. These rights are implemented on the principle of equality, the citizen is the main subject and the center of all library activities.     To ensure the exercise of this right, the Library Act prescribes measures to ensure the right of citizens to access information in libraries. These regulations carry an important meaning in facilitating citizens' access to information, and at the same time in line with the trend of the world.